2019
DOI: 10.1021/acsomega.9b00289
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Photoresponse Properties, and Biological Activity of Dicyano-Substituted 4-Aryl-2-pyridone Derivatives

Abstract: Described in this work is the synthesis of a novel dicyano-substituted N -2-aminoethyl-4-(3-pyridinyl)-2-pyridone organic compound ( 1 ) that is characterized by several spectroscopic methods. Compound ( 1 ) was utilized for the preparation of its perchlorate ( 2 ), chloride ( 3 ), and bromide ( 4 ) salts. Single-crystal X-ray structures of these three salts were determined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…However, the conduction band is dominated by the p-character of the 2-amino-4-methylpyridine ligands. Hexafluorophosphate anions do not directly influence the upper and lower states of the BG in agreement with other hybrid materials. …”
Section: Resultssupporting
confidence: 77%
“…However, the conduction band is dominated by the p-character of the 2-amino-4-methylpyridine ligands. Hexafluorophosphate anions do not directly influence the upper and lower states of the BG in agreement with other hybrid materials. …”
Section: Resultssupporting
confidence: 77%
“…15). [55][56][57][58][59][60] To calculate the optical response and taking into consideration the calculated band structure (Fig. 13), we have chosen a photon-energy range of 0-10 eV.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…It was observed that the compound can bind to the DNA helix in a partial intercalative manner. [26] Density functional theory (DFT) calculations in conjugation with molecular docking analysis are inevitable in exposing the nature of interactions between compounds and protein in recent years. [27,28] It is important to note that various forces including hydrogen bonding, π-π stacking, and electrostatic interactions along with other non-covalent interactions help the molecules to be intact inside the binding pocket of proteins.…”
Section: Introductionmentioning
confidence: 99%